Pesticide Labeling: Identification Numbers - Frederick M. Fishel (EDIS)
This document describes identification numbers seen on the pesticide label. Examples of various identification numbers are provided and their meanings explained. This document is PI-108, one of a series of the Agronomy Department, UF/IFAS Extension. Original publication date March 2006.